PROSPECTS FOR USE OF STRENGTH EXERCISES UNDER UNSTABLE WORK POSTURE AS A METHOD OF INCREASING STRENGTH ABILITIES IN HIGHLY QUALIFIED BIATHLONISTS - Kryuchkov, A.S.; Fedotova, E.V.; Sidelev, P.A.; Myakinchenko, E.B. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal, on the basis of a theoretical analysis, training effects when using strength exercises in an unstable working posture and to evaluate the prospects for their use as a method of increasing the specific strength of highly qualified biathletes. Methods and structure of the study. To solve the problems of the study, a systematic review and analysis of foreign scientific and methodological literature on the problems of strength training was carried out. Results and conclusions. The obtained results of scientific work made it possible to single out as the most significant effects of neuromuscular adaptation when performing strength exercises in an unstable working posture, first of all, improvement of the reciprocal innervation of agonist-antagonists and synchronization of the activity of agonists, synergists and stabilizer muscles. In this regard, strength exercises performed under conditions of an unstable support or with weights that create a multidirectional instability of the movement trajectory can be considered as a promising methodological solution to the problem of increasing the strength abilities of highly qualified biathletes.